Maximal Solvable Leibniz Algebras with a Quasi-Filiform Nilradical - Kobiljon Abdurasulov; Jobir Adashev; Ivan Kaygorodov (Mathematics, 2023)
This article is part of a study on solvable Leibniz algebras with a given nilradical. In this paper, solvable Leibniz algebras, whose nilradical is naturally graded quasi-filiform algebra and the complemented space to the nilradical has maximal dimension, are described up to isomorphism.